Analysis of Abu Yusuf's Thoughts on Tax Revenue in the Book of al-Kharāj and Its Relevance to Contemporary Tax Law Principles: A Fiqh Perspective - Jajat Sudrajat; Almurni, Muhammad Furqon; Yadi Janwari; Dedah Jubaedah (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2024)
This article aims to analyze the differences of opinion among scholars regarding the legal imposition of obligations on the public by the Islamic state other than zakat. The main focus of this article is on the views of Abu Yusuf, a prominent scholar during the Abbasid era, whose famous work al-Kharāj made a significant contribution to the development of the tax system in the Islamic state, as well as its relevance to contemporary tax law principles. In addition, the article examines the criteria for tax collection based on the perspective of fiqh. This study employs a qualitative approach using normative juridical and descriptive-analytical methods. The findings reveal that Abu Yusuf, through al-Kharāj, recognized the imposition of taxes by the state in addition to zakat, such as jizyah (a tax levied on non-Muslim citizens), ‘usyr (a tithe, typically one-tenth of agricultural produce), and kharāj (a land tax on agricultural lands). During the time of Prophet Muhammad PBUH there were no established regulations regarding kharāj and ‘usyr. The implementation of these two taxes began during the era of ‘Umar bin al-Khaṭṭāb RA, following the conquest of Persian territories, particularly the fertile region of Sawad in Iraq, where kharāj was imposed on land and ‘usyr was levied on non-Muslim traders entering Islamic territories. The conclusion of this study is that the imposition of taxes other than zakat is recognized in fiqh, provided it meets specific criteria, including a real and urgent need, fair and prudent implementation, allocation of tax revenue for public interest, and consultation between the leader and experts prior to tax imposition. The practical implication of this study is that the application of taxes in accordance with fiqh criteria can serve as an additional source of revenue for Islamic states to develop infrastructure and improve social welfare, particularly in efforts to alleviate poverty.